2014
DOI: 10.1007/s12671-014-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training Staff in MBPBS on the Use of Physical Restraints, Staff Stress and Turnover, Staff and Peer Injuries, and Cost Effectiveness in Developmental Disabilities

Abstract: Some individuals with developmental disabilities who reside in community group homes occasionally engage in low-frequency, but high-intensity, aggressive behavior. Over time, staff members assigned to manage the aggressive behaviors of these individuals are repeatedly injured, have to take time off work, become highly stressed, and eventually find alternative employment. In this study, we provided a 7-day intensive Mindfulness-Based Positive Behavior Support (MBPBS) training to staff from three group homes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 27 publications
9
72
0
Order By: Relevance
“…This parallels previous research indicating that in addition to the almost immediate physiological and psychological outcomes of mindfulness meditation, extended practice further increases the benefits of the procedure (Baron Short et al 2010;BrefczynskiLewis et al 2007;Lykins and Baer 2009). Conversely, whilst extended practice may be considered best practice, Singh et al (2014a) demonstrated the potential impact of only 7 days of intensive MBPBS in training staff caring for individuals with developmental disabilities. Not only did MBPBS produce positive results for carers, and for the individuals that they were caring for, these researchers were also able to demonstrate the cost effectiveness of the procedure within a 40 week time frame.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This parallels previous research indicating that in addition to the almost immediate physiological and psychological outcomes of mindfulness meditation, extended practice further increases the benefits of the procedure (Baron Short et al 2010;BrefczynskiLewis et al 2007;Lykins and Baer 2009). Conversely, whilst extended practice may be considered best practice, Singh et al (2014a) demonstrated the potential impact of only 7 days of intensive MBPBS in training staff caring for individuals with developmental disabilities. Not only did MBPBS produce positive results for carers, and for the individuals that they were caring for, these researchers were also able to demonstrate the cost effectiveness of the procedure within a 40 week time frame.…”
Section: Discussionsupporting
confidence: 80%
“…However, further research on this is clearly warranted. Systematic replications examining Mindful Parenting and child mindfulness effects in parallel, perhaps including physiological measures of the effects of the intervention and of Singh et al (2014a) Mindfulness-Based Positive Behavior Support (MBPBS) study through examining the cost benefits of such training with parents and carers of children with ASD would strengthen this evidence base substantially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly the facilities in charges are not given any administrative allowances thus felt demotivated. This study agrees with [24] [25]. One thing that could help retain employees and help decrease absenteeism is employee recognition programs [26].…”
Section: Personal Factors Contributing To Health Staff Absenteeismsupporting
confidence: 86%
“…), a meditation‐based approach that emphasises combining meditation with mindfulness, yoga and body awareness to cope with pain and stressors; and mindfulness‐based positive behaviour supports (Singh et al . ; Singh et al . ), which target mindful approaches to responding to problem behaviour in care recipients with DD.…”
Section: Discussionmentioning
confidence: 97%